A simple, reliable and accurate approach for assessing [131I]-capsule activity leading to significant reduction of radiation exposure of medical staff during radioiodine therapy. (April 2022) - Zuhayra, Maaz; Helm, Alexander; Ranjan, Joshua; Jüptner, Michael; Zhao, Yi; Marx, Marlies; Assam, Isong; Alfteimi, Ammar; Lützen, Ulf
Highlights: Measuring the [ 131 I]-capsule activity without opening the original delivery lead container. Accurate and reliable method. Substantial reduction of hands radiation exposure with respect to measuring in a dose calibrator. Abstract: Purpose: According to German law, the [ 131 I]-capsule activity has to be checked in the context of radioiodine therapy (RIT) immediately before application. The measurement leads to significant radiation exposure of the medical personnel, especially of their hands. We aimed to establish a method for estimating [ 131 I]-capsule activity by measuring the dose rate (DR) at contact of the delivered lead closed container carrying the [ 131 I]-capsules and to evaluate radiation exposure in comparison to conventional [ 131 I]-capsule measurement using a dose calibrator. Methods: DR on the surface of the closed lead container was measured at two locations and correlated linearly with the [ 131 I]-capsule activity measured in a dose calibrator to create calibrating curves. The hand and whole body (effective) doses were determined with official dose meters during validation of our method in clinical practice. Results: The determination coefficients (R 2 ) of linear calibration curves were greater than 0.9974. The total relative uncertainty for estimating [ 131 I]-capsule activity with our method was <±7.5% which is lower than the uncertainty of the nominal activity and quite close to the threshold limit for the maximum allowed uncertainty of ± 5% for measuring activity in radioactive drugs. The reduction of the hand dose caused by our method was 97% compared with the conventional measurements of the [ 131 I]-capsules in a dose calibrator. Conclusion: Measuring DR on the surface of the closed lead containers enables the [ 131 I]-capsules activity to be estimated simply, reliably and with sufficient accuracy leading to significant reduction of the radiation exposure for the medical staff.